Urea-loaded biochar at optimal pyrolysis temperature reshapes soil microbial communities to improve nitrogen use efficiency and mitigate environmental pollution in water spinach (Ipomoea aquatica Forsk.) - Muhammad Usman Ghani; Mengjun Li; Jian Shen; Yingting Gong; Ronghui Wang; Yinghui Xu; Muhammad Kamran; Shree Prakash Pandey; Shaoying Ai (Soil and Tillage Research, 2026)

Low-frequency polarized electric field promotes stilbene biosynthesis by redirecting phenylpropanoid flux in postharvest grapes - Jie Zhu; Huangqiao Tao; Shi Chen; Linyu Nian; Mengjun Wang; Fei Li; Xu Lu; Chongjiang Cao (Food Chemistry, 2026)

Regulation of mycelium–egg white protein composite formation by pH and ionic strength - Mukadaisi Muhedaner; Ziqing Song; Na Huang; Mengjun Li; Guanghong Zhou; Keping Ye (Food Bioscience, 2026)

Prenatal parabens exposure and infantile Eczema: Mediation by IL-17A, effect modification by breastfeeding, and evidence from network toxicology - Mengjun Chang; Xianjia Li; Ye Li; Yueyi Lv; Jin Ji; Can Liu; Guoai Yu; Xingyu Liao; Jie Gao; Leina Jia; Suzhen Guan (Environmental Pollution, 2026)

Rational Ba doping induces multiphase architecture in PrNi0.5Co0.5O3-δ for enhanced triple conductivity in protonic ceramic electrochemical cells - Mengjun Tang; Xiao Zhang; Waqas Muhammad; Yinghua Niu; Sheng Ma; Zuorui Xin; Jiaqi Wang; Tingting Liu; Mian Li; Liping Dai; Jinquan Wang; Zihao Xu; et al. (Chemical Engineering Journal, 2026)

Direct upcycling spent LiCoO2 into self-supporting cathodes via cobalt-seed induced slurry electrolysis - Yunhui Han; Xiangfei Zeng; Dejun He; Jiqin Wang; Kun Li; Qian Liang; Ling Hu; Anlong Han; Hao Li; Mengjun Chen (Chemical Engineering Journal, 2026)

Improving real-time PPP time transfer with the augmentation of predicted tropospheric products - Wei Xie; Kan Wang; Mengyuan Li; Zi Chen; Guolin Liu; Mengjun Wu; Xiaolong Mi; Xuhai Yang (GPS Solutions, 2026)
Real-time precise point positioning (PPP) time transfer is a crucial technique for the time and frequency field. However, its performance remains limited by the relatively long convergence time resulting from unstable parameter estimation in the initial stage. In this contribution, predicted tropospheric products provided by the Global Forecast System (GFS) are employed to derive predicted Zenith Wet Delays (ZWDs) for each station. The predicted ZWDs are subsequently incorporated into the real-time PPP as virtual observations, thereby enhancing the performance of the real-time PPP time transfer. One week of data from 20 globally distributed stations was used to form 19 time links. Results showed that the average root mean square error (RMSE) for the predicted ZWD amounts to 1.4 cm. For the traditional PPP strategy with ZWD estimation, the average convergence time of all links is 7.18 and 9.24 min for the static and kinematic modes, respectively. With the ZWD augmentation, they are shortened to 5.77 and 7.26 min, with improvements of 19.6% and 21.4%, respectively. In terms of the time link precision, the traditional and GFS ZWD-augmented methods yield 0.483 and 0.414 ns in the static mode, and 0.607 and 0.508 ns in the kinematic mode, with improvements of 14.3% and 16.3%, respectively. Regarding time link stability, improvements range from 10.0 to 20.6% in the static mode and from 9.7 to 21.4% in the kinematic mode when the averaging time is from 30 to 3600 s. These results clearly demonstrate that incorporating ZWD as external constraints can significantly enhance real-time PPP time transfer, particularly during the convergence period.

Advances in detection technologies for procymidone residues: From conventional methods to innovative approaches - Qiushuang Ai; Yifan Dong; Xiren Yu; Lijuan Yuan; Li Zhang; Mengjun Ye; Jianjun Xiang; Qiegen Liao; Jingtian Liang; Huming Shao; Dawen Zhang; Suyan Qiu (Food Control, 2026)

Resilient bioconversion of nitrite-rich organic wastes by black soldier fly larvae: Detoxification mechanisms and microbiome-mediated nitrogen cycling - Chaowei Qin; Mengjun Long; Jiabao Chen; Dan Shao; Shanshan Zhao; Long Chen; Zhenyu Zhang; Lijun Duan; Huan He; Juan Cortes Ortiz; Hui Wei; Qing Li; et al. (International Biodeterioration & Biodegradation, 2026)

Hydration mechanism, mechanical properties and environmental performance of electrolytic manganese residue based total solid waste supersulfate cement - Dejun He; Junying Li; Guiji Tu; Mengjun Chen; Yunhui Han (Process Safety and Environmental Protection, 2026)

New Insights into the multifunctional mechanisms of polyaniline/Fe₃O₄-biochar in anaerobic co-digestion: Electron shuttling, microbial community succession, and metabolic regulation - Boyang Li; Sijia Chen; Jinzhi Zou; Jianwei Zhao; Jinxu Zhang; Mengjun Zeng; Yingjie Sun; Weidong Ye (Process Safety and Environmental Protection, 2026)

Comparative Analysis of Sensory Quality and Microbial Communities Between Medium–High- and High-Temperature Daqu From Shangqiu Region - Mengjun Cui; Yurong Wang; Jixiang Sun; Jun Zhang; Haibao Fan; Yanju Li; Zhuang Guo; Huijun Zhao (Current Microbiology, 2026)

Gibberellin delays the red-turning of jujube fruit during storage via browning inhibition: Insights from targeted metabolomics - Tianyu Li; Jiaqi Liu; Jialin Tao; Tong Wu; Mengjun Liu; Shoukun Han (Postharvest Biology and Technology, 2026)

Electrochemical oscillation on lead recovery from spent lead paste by suspension electrolysis - Xingyu Luo; Jiqin Wang; Dejun He; Yunhui Han; Xiangfei Zeng; Ling Hu; Qian Liang; Hao Li; Anlong Han; Jianchen Shu; Mengjun Chen (Journal of Environmental Chemical Engineering, 2026)

A pilot-scale certification for copper recovery from waste printed circuit boards by NH3-NH4Cl-CuSO4 slurry electrolysis: perspective but challenge - Qian Liang; Ling Hu; Xiangfei Zeng; Jinchuan Qin; Yunhui Han; Huimin Yang; Huan Li; Xingyu Luo; Shuyuan Chen; Shaoqin Chen; Jiqin Wang; Jiancheng Shu; et al. (Journal of Environmental Chemical Engineering, 2026)

Rational design of CRISPR–Cas12a crRNAs for enhanced allelic discrimination and low-abundance variant detection - Wei Wu; Yijie Gong; Mengjun Deng; Manlu Yang; Lifeng Wang; Yuanyuan Wang; Li Yang; Xueping Chen; Guoming Xie; Junjie Li (Chemical Engineering Journal, 2026)

Paeoniflorigenone inhibits the progression of cholangiocarcinoma via HIF1A and enhances the chemotherapy sensitivity of cisplatin - Qing Hu; Mengqin Xiang; Feicheng Yang; Wei Guo; Mengjun Mo; Zhou Yang; Yanchun Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Silicon accumulation in Dendrocalamus ronganensis leaves: Monthly variability and environmental sensitivity - Rencheng Li; Mengjun Hu; Xiaofang Chen; Jun Fan; Ying Zhang; Zongyu Xiao; Yuzhe Wu; Xiajuan Li (Plant and Soil, 2026)

Rapid grouting evaluation with magnetic detection: Methods and mechanisms - Botao Wang; Jiacheng Zhang; Luoluo Song; Zhiheng Wang; Rentai Liu; Xiuhao Li; Shihao Luo; Mengjun Chen; Jiwen Bai (Journal of Applied Geophysics, 2026)

Sensory-metabolomics insights into quality alteration of dried jujube (Ziziphus jujuba ‘Huizao’) fruit in prolonged storage - Ye Yuan; Lili Li; Jiamin Li; Xiaojuan Yang; Shoule Wang; Bingqi Shen; Chong Chen; Juan Jin; Lei Yang; Dingyu Fan; Mengjun Liu; Zhihui Zhao; et al. (Food Chemistry, 2026)

Sr(Ⅱ) and Cs(Ⅰ) adsorbed by graphene synthesized from spent lithium-ion batteries anode materials via novelly electrochemical exfoliation - Xingying Fan; Xiangfei Zeng; Yunhui Han; XingYu Luo; Huan Li; Xingyu Xiao; Jin Bai; Mengjun Chen (Journal of Environmental Radioactivity, 2025)

Topography regulates soil extracellular enzyme activities through soil properties, and affects microbial resource limitations through hydroclimate in arid riparian forests - Mengjun Qu; Yin Wang; Xun Lei; Jianming Wang; Jingwen Li (Journal of Environmental Management, 2025)

The co-incorporation of rice straw and Chinese milk vetch enhances soil carbon retention by regulating the transformation of labile organic carbon fractions in paddy fields - Wangwang Zhang; Yuhong Wu; Fei Xu; Yuhang Qin; Hao Chen; Lv Wang; Mengjun Hu; Shuo Li (European Journal of Agronomy, 2025)

Rewiring photosynthetic carbon flow: Engineered cyanobacterial factories for sustainable carbohydrate production and carbon-negative biomanufacturing - Xinyi Bai; Guangbao Zhang; Libo Xu; Kang Li; Mengjun Zhang; Yi Huang (Bioresource Technology, 2025)

A rapid and ultrasensitive CRISPR/Cas12a-based assay for the accurate identification of T-even type phages - Chenhang Jiang; Yang Li; Ping Yu; Mengjun Fang; Di Huang; Xiangming Fang; Zhinan Xu (Biotechnology Letters, 2025)

Ultra-sensitive detection of complex SNVs via allele-specific dPCR enhanced by multi-strand displacement reaction - Mengjun Deng; Xueping Chen; Guoming Xie; Junjie Li (Chemical Engineering Journal, 2025)

Characteristics of lipid accumulation induced by high-altitude environment improve the total antioxidant capacity of Ophiocordyceps sinensis - Tao Wang; Chuyu Tang; Mengjun Xiao; Min He; Yuling Li; Xiuzhang Li (Food Chemistry, 2025)

Unlocking the nonlinear TOD-metro ridership relationship: A novel machine learning approach embedding spatiotemporal heterogeneity - Yun Luo; Bozhao Li; Hui Zhang; Mengjun Kang; Shiliang Su (Journal of Transport Geography, 2025)

Strengthening mechanism of water content reduction in electrolytic manganese residue by sodium oleate - Jing Wang; Zihan Li; Jiancheng Shu; Zongchen Wei; Shaoqin Chen; Hongyuan Zhao; Jun Luo; Huimin Yang; Yanyan You; Mengjun Chen; Yong Yang (Journal of Environmental Chemical Engineering, 2025)

Multiscale periodic analysis of sunspot number data and F10.7 index - Yi Shen; Chunmei Zhao; Peicheng Li; Mengjun Hu; Bingbing Zhang; Wang Li (Advances in Space Research, 2025)

Gibberellin and shikimic acid enhance ascorbic acid accumulation and ROS scavenging ability to delay the senescence of postharvest jujube fruit - Kangning Jiang; Xiaohuan Zhang; Tianyu Li; Jiaqi Liu; Mengjun Liu; Shoukun Han (Postharvest Biology and Technology, 2025)

Transcriptomics and metabolomics provide the difference of unique odor between natural and cultivated Ophiocordyceps sinensis and the biosynthetic pathway of key volatile compounds - Tao Wang; Mengjun Xiao; Chuyu Tang; Jianzhao Qi; Yuling Li; Xiuzhang Li (Food Bioscience, 2025)

Characterization and Assessment of Sheep-Origin Probiotic Bacillus licheniformis B63 Strain for Potential Use in Intestinal Health and Disease - Meng Hou; Yabin Lu; Mengjun Ye; Na Li; Yawei Sun; Gang Yao; Jinquan Wang; Fangfang Yin; Qimin Peng; Sheng Jia; Rui Shi; Xuxiang Wang (Probiotics and Antimicrobial Proteins, 2025)

Screening of Spinal Muscular Atrophy Carriers and Prenatal Diagnosis in Pregnant Women in Yancheng, China - Huilin Sun; Jianli Zheng; Qing’e Zhang; Feifei Ying; Yadong Fu; Yongjuan Guan; Jing Wu; Yueyun Zhou; Jingjing Dong; Mengjun Xu; Fangfang Yang; Ning An; et al. (Biochemical Genetics, 2025)

Corrigendum to “Atmospheric microplastic input into wetlands: Spatiotemporal patterns, drivers, and unique ecological impacts” [Water Research, 268 (2025): 122601] - Libo Xu; Xudong Tian; Xinyi Bai; Kang Li; Guangbao Zhang; Mengjun Zhang; Matthias C. Rillig; Yi Huang; Min Hu (Water Research, 2025)

Residue depletion and withdrawal time estimation of tilmicosin in black-bone silky fowls after administration via drinking water - Li Zhang; Lijuan Yuan; Mengjun Ye; Jianjun Xiang; Yifan Dong; Qiegen Liao; Suyan Qiu; Dawen Zhang; Xiren Yu (Food Additives & Contaminants: Part A, 2025)

Atmospheric microplastic input into wetlands: Spatiotemporal patterns, drivers, and unique ecological impacts - Libo Xu; Xudong Tian; Xinyi Bai; Kang Li; Guangbao Zhang; Mengjun Zhang; Matthias C. Rillig; Yi Huang; Min Hu (Water Research, 2025)

Direct evidence for selective microbial enrichment with plastic degradation potential in the plastisphere - Xinyi Bai; Kang Li; Libo Xu; Guangbao Zhang; Mengjun Zhang; Yi Huang (Science of The Total Environment, 2024)

Regulation of skin pigments in winter jujube fruit treated with elevated O2 - Dong Li; Wenxuan Li; Qingqing Wang; Yanpei Chen; Yanqun Xu; Xingtao Zhang; Zhihui Zhao; Mengjun Liu; Qinyang Cheng; Zisheng Luo (Postharvest Biology and Technology, 2024)

Sandstorms contribute to the atmospheric microplastic pollution: Transport and accumulation from degraded lands to a megacity - Libo Xu; Xinyi Bai; Kang Li; Guangbao Zhang; Mengjun Zhang; Zhijun Wu; Yi Huang; Min Hu (Journal of Hazardous Materials, 2024)

Fire alters soil bacterial and fungal communities and intensifies seasonal variation in subtropical forest ecosystem - Ziyue Shi; Yaru Chen; Aogui Li; Mengjun Hu; Weixing Liu (European Journal of Soil Biology, 2024)

Cobalt nanoparticles attenuate microplastic-induced vascular endothelial injury via Nrf2 pathway activation - Linhua Deng; Mengjun Li; Zhongjing Jiang; Gang Xiang; Sihan He; Hongqi Zhang; Ang Deng; Yunjia Wang (Science of The Total Environment, 2024)

Torsional vibration analysis and fuzzy adaptive PID control optimization of underwater vector propulsion shaft systems - Zhengyu Chen; Yingchun Jia; Mengjun Wang; Shuaishuai Li; Songmei Li (Ocean Engineering, 2024)

Recovery of bacterial network complexity and stability after simulated extreme rainfall is mediated by K−/r-strategy dominance - Yin Wang; Mengjun Qu; Jianming Wang; Weilin Zhu; Jingwen Li (Applied Soil Ecology, 2024)

Decoding the biochemical dialogue: metabolomic insights into soybean defense strategies against diverse pathogens - Min Qiu; Mengjun Tian; Yaru Sun; Huaibo Li; Wenwen Huang; Haibing Ouyang; Shaoyan Lin; Chen Zhang; Ming Wang; Yuanchao Wang (Science China Life Sciences, 2024)

Analysis of binding and authentic virus-neutralizing activities of immune sera induced by various monkeypox virus antigens - Shuo Song; Zuning Ren; Jiayin Chen; Mengjun Li; Yushan Jiang; Yingxia Liu; Bao Zhang; Hongzhou Lu; Wei Zhao; Chenguang Shen; Yang Yang (Immunologic Research, 2024)

Taxonomic turnover dominates changes in soil microbial communities and functions in response to wildfire in subtropical forest - Ziyue Shi; Yaru Chen; Aogui Li; Chao Wang; Mengjun Hu; Weixing Liu (Applied Soil Ecology, 2024)

Changes in soil bacterial community diversity and its network stability under different grazing intensities in plateau rangelands - Mengjun Liu; Qing Yang; Bingjie Yan; Yue Ren; Xiaodong Li; Shiying Zhu; Migmar Wangdwei (Agriculture, Ecosystems & Environment, 2024)

Coordinated responses of rice (Oryza sativa) to the stresses of benzotriazole ultraviolet stabilizers (BZT-UVs): Antioxidative system, photosynthetic activity, and metabolic regulation - Huijun Liu; Mengjun Wang; Siyuan Jin; Qian Guo; Shuping Wang; Haohua Ni; Hainan Lu; Zhiheng Li (Journal of Hazardous Materials, 2024)

Nanocluster-agminated amorphous cobalt nanofilms for highly selective electroreduction of nitrate to ammonia - Minghang Jiang; Mengfei Zhu; Junjie Ding; Huaizhu Wang; Qianchuan Yu; Xi Chen; Yi He; Mengjun Wang; Xiaojun Luo; Caijun Wu; Liyun Zhang; Xinghui Yao; et al. (Journal of Hazardous Materials, 2024)

Disruption of microbiota induced by polyethylene microplastics alters defense response of earthworms Eisenia fetida - Kang Li; Mengjun Zhang; Libo Xu; Guangbao Zhang; Xinyi Bai; Weishuang Zheng; Yi Huang (Applied Soil Ecology, 2024)

Multi-Scale Higher-Order Dependencies (MSHOD): Higher-Order Interactions Mining and Key Nodes Identification for Global Liner Shipping Network - Yude Fu; Xiang Li; Jichao Li; Mengjun Yu; Xiongyi Lu; Qizi Huangpeng; Xiaojun Duan (Journal of Marine Science and Engineering, 2024)
Liner shipping accounts for over 80% of the global transportation volume, making substantial contributions to world trade and economic development. To advance global economic integration further, it is essential to link the flows of global liner shipping routes with the complex system of international trade, thereby supporting liner shipping as an effective framework for analyzing international trade and geopolitical trends. Traditional methods based on first-order global liner shipping networks, operating at a single scale, lack sufficient descriptive power for multi-variable sequential interactions and data representation accuracy among nodes. This paper proposes an effective methodology termed “Multi-Scale Higher-Order Dependencies (MSHOD)” that adeptly reveals the complexity of higher-order interactions among multi-scale nodes within the global liner shipping network. The key step of this method is to construct high-order dependency networks through multi-scale attributes. Based on the critical role of high-order interactions, a method for key node identification has been proposed. Experiments demonstrate that, compared to other methods, MSHOD can more effectively identify multi-scale nodes with regional dependencies. These nodes and their generated higher-order interactions could have transformative impacts on the network’s flow and stability. Therefore, by integrating multi-scale analysis methods to mine high-order interactions and identify key nodes with regional dependencies, this approach provides robust insights for assessing policy implementation effects, preventing unforeseen incidents, and revealing regional dual-circulation economic models, thereby contributing to strategies for global, stable development.

The potential benefits and mechanisms of protein nutritional intervention on bone health improvement - Yonghui Yu; Xinping Li; Mengjun Zheng; Linyue Zhou; Jingjie Zhang; Jing Wang; Baoguo Sun (Critical Reviews in Food Science and Nutrition, 2024)

c-Jun targets miR-451a to regulate HQ-induced inhibition of erythroid differentiation via the BATF/SETD5/ARHGEF3 axis - Yanrong Lv; Xiaoju Ma; Qing Liu; Zihao Long; Shuangqi Li; Zhaoqing Tan; Dongsheng Wang; Xiumei Xing; Liping Chen; Wen Chen; Qing Wang; Qing Wei; et al. (Toxicology, 2024)

Empirical analysis of lead neurotoxicity mode of action and its application in health risk assessment - Hehai Huang; Yanrong Lv; Qingfei Chen; Xiaowei Huang; Jingyao Qin; Yan Liu; Qilong Liao; Xiumei Xing; Liping Chen; Qing Liu; Shuangqi Li; Zihao Long; et al. (Environmental Research, 2024)

Preparation of anti-washout cement-stabilized marine soft clay for scouring protection of wind power pile foundations - Xiuhao Li; Zhijing Zhu; Rentai Liu; Chunyu Zhang; Qingsong Zhang; Shucai Li; Mengjun Chen (Marine Georesources & Geotechnology, 2024)

Preparation, characterization and in vitro digestion of jujube polysaccharide microcapsules - Qingyi Li; Meiling Liu; Mengjun Liu; Huiqiang Wang; Zhihui Zhao (Food and Bioproducts Processing, 2024)

8-OHdG mediates the association of co-exposure to fifty-five typical endocrine-disrupting chemicals with renal function: a cross-section investigation in Southern Chinese adults - Qingfei Chen; Qifei Deng; Qilong Liao; Yan Liu; Zhaorui Zhang; Dehua Wu; Yanrong Lv; Jingyao Qin; Qing Liu; Shuangqi Li; Zihao Long; Xiumei Xing; et al. (Environmental Science and Pollution Research, 2024)

Photoaged microplastics enhanced the antibiotic resistance dissemination in WWTPs by altering the adsorption behavior of antibiotic resistance plasmids - Qian Guo; Mengjun Wang; Siyuan Jin; Haohua Ni; Shuping Wang; Jie Chen; Wenlu Zhao; Zhiguo Fang; Zhiheng Li; Huijun Liu (Science of The Total Environment, 2024)

The spatial transcriptomic landscape of human gingiva in health and periodontitis - Zongshan Shen; Ran Zhang; Yunjia Huang; Jiayao Chen; Mengjun Yu; Chunhua Li; Yong Zhang; Lingling Chen; Xin Huang; Jichen Yang; Zhengmei Lin; Songlin Wang; et al. (Science China Life Sciences, 2024)

Predicting Drug-Drug Interactions Involving Rifampicin Using a Semi-mechanistic Hepatic Compartmental Model - Jingxi Li; Xue Li; Keheng Wu; Sihui Long; Youni Zhao; Xiong Jin; Mengjun Zhang; Xinyi Wu; Zhijun Huang; Zhou Zhou; Jack Liu; Bo Liu (Pharmaceutical Research, 2024)

Potential environmental risks of field bio/non-degradable microplastic from mulching residues in farmland: Evidence from metagenomic analysis of plastisphere - Kang Li; Libo Xu; Xinyi Bai; Guangbao Zhang; Mengjun Zhang; Yi Huang (Journal of Hazardous Materials, 2024)

Integrated assessment and prediction of ecological security in typical ecologically fragile areas - Ling Lv; Wei Guo; Xuesheng Zhao; Jing Li; Xianglin Ji; Mengjun Chao (Environmental Monitoring and Assessment, 2024)

Deciphering the evolving trajectories of China's megaregions from 1992 to 2020: A novel morphological approach based on global land cover products - Haojie Cao; Yu Li; Min Weng; Shiliang Su; Mengjun Kang (Applied Geography, 2024)

Polyhydroxyalkanoates (PHAs) biological recovery approaches and protein-mediated secretion model hypothesis - Guangbao Zhang; Weishuang Zheng; Xinyi Bai; Libo Xu; Kang Li; Mengjun Zhang; Yi Huang (Journal of Cleaner Production, 2024)

Construction and optimization of ecological network in inland river basin based on circuit theory, complex network and ecological sensitivity: A case study of Gansu section of Heihe River Basin - Aokang Xu; Mengjun Hu; Jing Shi; Qingzhu Bai; Xuehong Li (Ecological Modelling, 2024)

Differential fungal assemblages and functions between the plastisphere of biodegradable and conventional microplastics in farmland - Kang Li; Libo Xu; Xinyi Bai; Guangbao Zhang; Mengjun Zhang; Yi Huang (Science of The Total Environment, 2024)

Microplastics in the atmosphere: Adsorb on leaves and their effects on the phyllosphere bacterial community - Libo Xu; Kang Li; Xinyi Bai; Guangbao Zhang; Xudong Tian; Qian Tang; Mengjun Zhang; Min Hu; Yi Huang (Journal of Hazardous Materials, 2024)

Synergistic harmless treatment of phosphogypsum leachate wastewater with iron-rich electrolytic manganese residue and electric field - Jiancheng Shu; Junjie Zhao; Xiaoqin Wei; Mengjun Chen; Bing Li; Yushi Gao; Yong Yang; Zongyu Deng (Minerals Engineering, 2023)

Soil Enzyme Activity and Stoichiometry Change with Perennial Mugwort Cropping Cultivation Year in Central China - Zhenxing Zhou; Xuedan Li; Zhaolin Sun; Mengjun Hu; Ying Li; Kunpeng Zhang; Shijie Han (Journal of Soil Science and Plant Nutrition, 2023)

Interkingdom ecological networks between plants and fungi drive soil multifunctionality across arid inland river basin - Yin Wang; Jianming Wang; Yicheng He; Mengjun Qu; Weilin Zhu; Yujie Xue; Jingwen Li (Molecular Ecology, 2023)
Despite the known collective contribution of above‐ (plants) and below‐ground (soil fungi) biodiversity on multiple soil functions, how the associations among plant and fungal communities regulate soil multifunctionality (SMF) differentially remains unknown. Here, plant communities were investigated at 81 plots across a typical arid inland river basin, within which associated soil fungal communities and seven soil functions (nutrients storage and biological activity) were measured in surface (0–15 cm) and subsurface soil (15–30 cm). We evaluated the relative importance of species richness and biotic associations (reflected by network complexity) on SMF. Our results demonstrated that plant species richness and plant–fungus network complexity promoted SMF in surface and subsurface soil. SMF in two soil layers was mainly determined by plant–fungus network complexity, mean groundwater depth and soil variables, among which plant–fungus network complexity played a crucial role. Plant–fungus network complexity had stronger effects on SMF in surface soil than in subsurface soil. We present evidence that plant–fungus network complexity surpassed plant‐fungal species richness in determining SMF in surface and subsurface soil. Moreover, plant–fungal species richness could not directly affect SMF. Greater plant–fungal species richness indirectly promoted SMF since they ensured greater plant–fungal associations. Collectively, we concluded that interkingdom networks between plants and fungi drive SMF even in different soil layers. Our findings enhanced our knowledge of the underlying mechanisms that above‐ and below‐ground associations promote SMF in arid inland river basins. Future study should place more emphasis on the associations among plant and microbial communities in protecting soil functions under global changes.

Plastic substrate and residual time of microplastics in the urban river shape the composition and structure of bacterial communities in plastisphere - Libo Xu; Kang Li; Mengjun Zhang; Jiabao Guo; Weiqian Jia; Xinyi Bai; Xudong Tian; Yi Huang (Journal of Environmental Management, 2023)

Al3+ intercalated NH4V4O10 nanosheet on carbon cloth for high-performance aqueous zinc-ion batteries - Ke Wang; Ruilong Yuan; Mengjun Li; Ying Huang; Wei Ai; Zhuzhu Du; Pan He; Binwu Wang (Chemical Engineering Journal, 2023)

Chlorine and heavy metals removal from municipal solid waste incineration fly ash by electric field enhanced oxalic acid washing - Hang Zhao; Feihua Yang; Zhaojia Wang; YinMing Li; Jianping Guo; Sha Li; Jiancheng Shu; Mengjun Chen (Journal of Environmental Management, 2023)

Electrolyte circulation: Metal recovery from waste printed circuit boards of mobile phones by alkaline slurry electrolysis - Qian Liang; Jiqin Wang; Shuyuan Chen; Shaoqin Chen; Ling Hu; Jinchuan Qin; Yunhui Han; Xiangfei Zeng; Xiaogang Li; Qingbin Guo; Mengjun Chen; Jiancheng Shu (Journal of Cleaner Production, 2023)

Evolution of Asian drying since 30 Ma revealed by clay minerals record in the West Pacific and its tectonic-climatic forcing - Yi Tang; Shiming Wan; Debo Zhao; Zhaojie Yu; Zhaokai Xu; Jin Zhang; Zehua Song; Mengjun Li; Hualong Jin; Wenjun Jiao; Hongkun Dong; Anchun Li (Science China Earth Sciences, 2023)

Evolution of silicate weathering in South China since 30 Ma: Controlling factors and global implications - Hualong Jin; Shiming Wan; Chang Liu; Debo Zhao; Wenqiang Pei; Zhaojie Yu; Jin Zhang; Zehua Song; Mengjun Li; Yi Tang; Anchun Li (Global and Planetary Change, 2023)

Expansion of C4 plants in South China and evolution of East Asian monsoon since 35 Ma: Black carbon records in the northern South China Sea - Mengjun Li; Shiming Wan; Christophe Colin; Hualong Jin; Debo Zhao; Wenqiang Pei; Wenjun Jiao; Yi Tang; Yang Tan; Xuefa Shi; Anchun Li (Global and Planetary Change, 2023)

Deep reinforcement learning method for satellite range scheduling problem - Junwei Ou; Lining Xing; Feng Yao; Mengjun Li; Jimin Lv; Yongming He; Yanjie Song; Jian Wu; Guoting Zhang (Swarm and Evolutionary Computation, 2023)

Soil fungal guilds as important integrators linking plant richness and carbon, nitrogen and phosphorus stocks in oasis–desert ecosystems - Yin Wang; Jianming Wang; Mengjun Qu; Shuai Shao; Jingwen Li (Soil Biology and Biochemistry, 2023)

Enhanced weathering input from South Asia to the Indian Ocean since the late Eocene - Zehua Song; Shiming Wan; Christophe Colin; Christian France-Lanord; Zhaojie Yu; Arnaud Dapoigny; Hualong Jin; Mengjun Li; Jin Zhang; Debo Zhao; Xuefa Shi; Anchun Li (Science Bulletin, 2023)

Deciphering the effects of LDPE microplastic films on diversity, composition and co-occurrence network of soil fungal community - Kang Li; Mengjun Zhang; Weiqian Jia; Libo Xu; Yi Huang (Applied Soil Ecology, 2023)

The plastisphere of biodegradable and conventional microplastics from residues exhibit distinct microbial structure, network and function in plastic-mulching farmland - Kang Li; Weiqian Jia; Libo Xu; Mengjun Zhang; Yi Huang (Journal of Hazardous Materials, 2023)

Solid-liquid interface adsorption of antibiotic resistance plasmids induced by nanoplastics aggravates gene pollution in aquatic ecosystems - Zhiheng Li; Mengjun Wang; Hong Fang; Zhangchao Yao; Huijun Liu; Wenlu Zhao; Jie Chen (Environmental Pollution, 2023)

Bioremediation of quinclorac injury on tobacco by a rhizosphere bacterium - Linhan Li; Ting Zhou; Linyu Zhong; Qian Zhou; Gang Gu; Mengjun Hu; Fengping Chen; Sheng Lin (World Journal of Microbiology and Biotechnology, 2022)

Radium isotope assessment of submarine groundwater discharge and associated nutrient inputs in Eastern Liaodong Bay, China - Qiaona Guo; Yue Zhao; Mengjun Li; Jinhui Liu (Frontiers in Marine Science, 2022)
The accurate assessment of submarine groundwater discharge (SGD) and associated nutrient fluxes plays a significant role in water resources management and ecological environment protection in the coastal area. Currently, Liaodong Bay has become one of the most polluted marine areas in China. However, the nutrient fluxes carried by the SGD and its environmental effects have not yet been thoroughly reported in eastern Liaodong Bay, China. In this study, the distribution of 224 Ra/ 223 Ra activity ratio and its influencing factors under the geochemical conditions were explored. The activity of radium was affected by the water type and the geochemical factors. The radium isotopes in seawater were positively correlated with the ratios of Mg 2+ /Na + and Ca 2+ /Na + but negatively correlated with salinity and SO 4 2− . The average apparent water age was evaluated to be 13.0 days. Furthermore, based on the radium mass balance model, the total average SGD flux was calculated to be 1.31 × 10 8 m 3 day –1 . The nutrient fluxes carried by the SGD were 7.16 × 10 7 , 1.01 × 10 6 , 1.61 × 10 7 , 0.92 × 10 6 , and 5.41 × 10 7 mol day −1 for DIN, DIP, NH 4 + , NO 2 − , and NO 3 − , respectively. The nutrient inputs through the SGD have an average DIN : DIP ratio of 70, which was able to seriously affect the ecological environment. The SGD-derived nutrient fluxes were higher than the local river input, which demonstrated that the SGD was a major source of nutrients affecting regional marine ecosystems.

Evaluation of a Superabsorbent Polymer for Plugging Karst Pipe Type Water Inrushes - Chenyang Ma; Shucai Li; Rentai Liu; Yan Pei; Chunyu Zhang; Yankai Liu; Fei Xu; Xiao Feng; Mengjun Chen (Mine Water and the Environment, 2022)

Identification and colonization dynamics of an antagonistic endophytic bacterium 262XY2′ against Pseudomonas syringae causing tomato leaf spot disease - Chengde Yang; Zhonghong Feng; Ying Wang; Mengjun Jin; Tonghua Li; JingJiang Zhou (European Journal of Plant Pathology, 2021)

Transcriptome analysis reveals the effects of temperature on growth in tadpoles of spiny-bellied frog (Quasipaa boulengeri) - Wenqiao Fan; Mengjun Huang; Jingming Xu; Meixia Zhang; Yusong Jiang; Mingcheng Cai; Hanchang Sun; Xiaoying Li (Aquaculture International, 2021)

The effect of salt on the evolution of a subsalt sandstone reservoir in the Kuqa foreland basin, western China - Hai Wu; Mengjun Zhao; Qingong Zhuo; Xuesong Lu; Long Wang; Weiqiang Li; Ya Deng (Carbonates and Evaporites, 2020)

The characteristics and genome analysis of vB_ApiP_XC38, a novel phage infecting Acinetobacter pittii - Mengjun Cheng; Man Luo; Hengyu Xi; Yunze Zhao; Shuai Le; Li-Kuang Chen; Demeng Tan; Yuan Guan; Tianqi Wang; Wenyu Han; Nannan Wu; Tongyu Zhu; et al. (Virus Genes, 2020)

Isolation and identification of a Bacillus subtilis HZ-72 exhibiting biocontrol activity against flax seedling blight - Taimeng Tan; Jiuxiang Zhu; Airong Shen; Jilie Li; Yongting Yu; Mengjun Zhang; Mengrui Zhao; Zhimin Li; Jia Chen; Chunsheng Gao; Yi Cheng; Litao Guo; et al. (European Journal of Plant Pathology, 2019)

Sophocarpine attenuates murine lupus nephritis via inhibiting NLRP3 inflammasome and NF-κB activation - Xiuzhen Li; Mengjun Wang; Hong Hong; Congjuan Luo; Zewei Liu; Ruiheng Yang (Immunologic Research, 2018)

Effects of soil moisture content on the growth and physiological status of ginger (Zingiber officinale Roscoe) - Honglei Li; Mengjun Huang; Dingquan Tan; Qinhong Liao; Yong Zou; Yusong Jiang (Acta Physiologiae Plantarum, 2018)

Decolorization of textile dye RB19 using volcanic rock matrix immobilized Bacillus thuringiensis cells with surface displayed laccase - Juan Wan; Xiaowen Sun; Cheng Liu; Mengjun Tang; Lin Li; Hong Ni (World Journal of Microbiology and Biotechnology, 2017)

Physiological and antioxidant responses of Basella alba to NaCl or Na2SO4 stress - Jianfeng Ning; Shaoying Ai; Shaohai Yang; Lihua Cui; Yong Chen; Lili Sun; Ronghui Wang; Mengjun Li; Zhaobing Zeng (Acta Physiologiae Plantarum, 2015)

Identification of TaWD40D, a wheat WD40 repeat-containing protein that is associated with plant tolerance to abiotic stresses - Dejing Kong; Mengjun Li; Zhanghui Dong; Hongtao Ji; Xia Li (Plant Cell Reports, 2015)

Association of obesity and overweight with overall survival in colorectal cancer patients: a meta-analysis of 29 studies - Shuangjie Wu; Jun Liu; Xinhai Wang; Mengjun Li; Yu Gan; Yifan Tang (Cancer Causes & Control, 2014)

Complete genome sequence of a novel infectious bronchitis virus strain circulating in China with a distinct S gene - Sheng Zhou; Mengjun Tang; Yi Jiang; Xu Chen; Xinyue Shen; Jianmei Li; Yabin Dai; Jianmin Zou (Virus Genes, 2014)

The application of hepatic P450 reductase null gpt delta mice in studying the role of hepatic P450 in genotoxic carcinogen 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone-induced mutagenesis - Yang Luan; Guozhen Xing; Xinming Qi; Mengjun Wu; Chenggang Li; Jun Yao; Likun Gong; Takehiko Nohmi; Jun Gu; Wanhong Zhou; Saijing Zheng; Jin Ren (Archives of Toxicology, 2012)